UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MEMBUAT PERANGKAT PEMBELAJARAN MELALUI PENDAMPINGAN DI SMP NEGERI 2 PASIR LIMAU KAPAS KABUPATEN ROKAN HILIR - Aminudin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to determine whether teachers’ ability to develop learning tools could be improved through mentoring at SMP Negeri 2 Pasir Limau Kapas. The focus of the research was on enhancing teachers’ competence in preparing learning tools through a structured mentoring process. The study employed classroom action research conducted at SMP Negeri 2 Pasir Limau Kapas, with the research process implemented under the supervision and mentoring of the school principal. This mentoring activity was aligned with the principal’s role in fostering teachers’ professional development, particularly in improving their ability to design effective learning tools. The research was conducted over two cycles within a period of one month. The results indicated that mentoring activities effectively improved teachers’ ability to create learning tools in each cycle. This finding was supported by the data obtained, which showed that in the first cycle, teachers’ ability reached 78.9%, categorized as good, and increased to 87.8% in the second cycle, also categorized as good. These results demonstrate that mentoring is an effective strategy for enhancing teachers’ ability to develop learning tools at SMP Negeri 2 Pasir Limau Kapas.